Effect of Curing Time on Micro shear Bond Strength of Enamel and Dentin Bonding Agents to Enamel - Ghasemi, Amir; Alam, Mostafa; Abbasi, Kamyar; Massoumi, Farhood; Shafiei, Shervin (Regeneration, Reconstruction & Restoration (Triple R), 2019)
Introduction: The bond strength to enamel may be simply improved by increasing the polymerization rate via prolonging the curing time. This study sought to assess the effect of increasing the curing time on microshear bond strength of enamel (Heliobond) and dentin (Excite) bonding agents to enamel. Materials and Methods: 90 extracted, sound human molar teeth randomly divided into six groups. In group 1, the enamel surfaces etched 30 seconds and were rinsed for 30 seconds. After drying, Heliobond was applied and light cured for 10 seconds, in groups 2 and 3, the curing time was 20 and 40 seconds, respectively. In group 4, specimens were prepared as in group 1 except that Excite dentin bonding agent was used. Groups 5 and 6 were prepared as in group 4 but the curing time was 20 and 40 seconds, respectively. The microshear bond strength of specimens was measured using micro tensile tester and analyzed. The mode of failure of specimens was evaluated under a microscope. Results: Two-way ANOVA showed significant differences in bond strength of Heliobond and Excite specimens cured for different times. However, no significant difference was noted in microshear bond strength of specimens cured for 10 and 20 seconds (neither in Excite nor in Heliobond groups). Pairwise comparison of groups revealed significant differences between specimens cured for 10 and 20 seconds with 40 seconds curing times. The overall microshear bond strength of specimens in Heliobond groups was significantly higher than that of Excite groups. The mode of failure of groups bonded with Heliobond and Excite was not significantly different. Conclusion: Within the limitations of this study, prolonging the curing time up to the certain time significantly increased the micro shear bond strength of both enamel (Heliobond) and dentin (Excite) bonding agents to enamel.